The employment of self-regulated reading strategies by English as a foreign language students in Vietnam - Lap, Trinh Quoc; Nguyen, Dang Kim; Tuan, Le Cong (Humanities, Arts and Social Sciences Studies, 2025)
Reading comprehension is a crucial component of academic life, especially for students majoring in English. However, EFL students face various challenges in their learning, including, for example, the interpretation of reading materials and a lack of motivation. In this respect, students could utilize self-regulated learning (SRL) strategies to increase their learning autonomy and motivation, which are believed to contribute to academic success. Given that Vietnamese EFL learners also apply SRL strategies, this study aims to investigate the degree to which English majors employ SRL strategies in reading. The study also attempts to examine the most and least frequently used strategies and the differences, if any, between the two genders regarding SRL strategy use. 130 English-majored students from a university in the Mekong Delta were involved in the study. The quantitative data were gathered using a closed-ended questionnaire adapted from Duong and Ta (2022), and a follow-up interview for qualitative data was conducted with five students randomly chosen from the participants. The findings revealed that students generally employed SRL strategies to enhance reading comprehension, with different levels across the eight subcategories of strategy. In addition, a statistical test showed no significant difference between the male and female students regarding their implementation of SRL strategies. These results suggest pedagogical implications for teachers and learners, emphasizing the importance of SRL strategies in developing reading skills. Thus, teachers are expected to raise students’ awareness and practical employment of SRL to achieve their academic goals.